ANALISIS PERCEPATAN TANAH PERMUKAAN DI WILAYAH RIAU DENGAN METODE PSHA - Elvis Saputra; Lalu Makrup; Fitri Nugraheni; Widodo . (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2020)
The western region of Sumatra Island is an area located on the world's active plate margin, which is reflected by the high frequency of earthquake events. An effort to reduce the impact of the earthquake disaster is to conduct a seismic hazard analysis. There have been many studies on seismic hazard in the West Sumatra region. Still, in the surrounding areas such as Riau, which borders directly with the territory, there has never been an earthquake hazard mapping micro zonation. This study aims to determine the value of surface acceleration for various districts or cities in Riau Province, by knowing the amount of surface acceleration, it will be able to identify the areas that have a relatively high level of earthquake risk. The Surface acceleration analysis is done by using the probabilistic Seismic hazard method (PSHA) using The SR Model software. The results of this study are obtained from 12 districts or cities located in Riau in which three areas have a high value of surface acceleration, those are Rokan Hulu regency, Kampar regency), and Kuantan Singingi regency). The amount of surface acceleration in Riau province in the 0.0 second period or peak ground acceleration (PGA) is in the range 0.097 - 0.78 g, then in the 0.2 second period the surface acceleration is in the range 0.204 – 1.943 g, and in the 1 second period of the surface acceleration is in the range 0.176 - 1.155 g.